(untitled) (Tribhuvan University Journal of Food Science and Technology, 2023)
Three phase partitioning (TPP), a novel and non-chromatographic method was effectively applied for the extraction and recovery of papain from Carica papaya latex. The effect of change in ammonium sulfate concentration, crude extract to solvent ratio and pH on extraction efficiency was studied, and these parameters were optimized by response surface methodology (RSM) using Box-Behnken Design. The protease was found to be concentrated more at the aqueous phase (AP) with 51.08% ammonium sulfate precipitation, crude extract to tert-butanol ratio of 1:0.78 (v/v), and pH 6.05 resulting 9.242 purification fold and 159.806% activity recovery. Compared to the intermediate phase (IP), the AP demonstrated higher recovery and purification fold. Purified papain showed significantly (p<0.05) greater activity at a temperature of 60°C and pH of 6.0. It also demonstrated stability within the temperature range of 40 to 70°C and pH range of 6.0 to 8.0. Enzyme retained maximum milk clotting activity when stored under freezing (-20°C) for 3 weeks. This study showed that the TPP can be used to extract and purify papain from papaya latex economically and it can also be employed as a vegetable coagulant for cheesemaking.